2023
DOI: 10.1093/jnci/djad159
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after patient-initiated vs physician-initiated response to symptom monitoring: the SYMPRO-Lung trial

Nicole E Billingy,
Vashti N M F Tromp,
Neil K Aaronson
et al.

Abstract: BACKGROUND Previous studies using patient-reported outcomes measures (PROMs) to monitor symptoms during and after (lung) cancer treatment used alerts that were sent to the healthcare provider (HCP), while an approach in which patients receive alerts could be more clinically feasible. The primary aim of this study was to compare the effect of weekly PROM symptom monitoring via a reactive approach (patient receives alert) or active approach (HCP receives alert) with care as us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With current limitations in staff and resources, a step-by-step implementation, linking (e)PROMs to referral pathways and other tools to support clinical decision-making, and piloting the protocol on a manageable sample of patients using small cycles of change may be the way forward [ 36 , 41 ]. A recent trial assessing the effect of patient-reported symptom monitoring on HRQOL in lung cancer patients, observed that a reactive approach (patient receives alert) and an active approach (health-care provider receives alert) are equally effective on HRQOL [ 42 ]. Because of time demands placed on HCP, a more patient-centered approach, focusing on self-monitoring and self-care can facilitate sustainable implementation of symptom monitoring within daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…With current limitations in staff and resources, a step-by-step implementation, linking (e)PROMs to referral pathways and other tools to support clinical decision-making, and piloting the protocol on a manageable sample of patients using small cycles of change may be the way forward [ 36 , 41 ]. A recent trial assessing the effect of patient-reported symptom monitoring on HRQOL in lung cancer patients, observed that a reactive approach (patient receives alert) and an active approach (health-care provider receives alert) are equally effective on HRQOL [ 42 ]. Because of time demands placed on HCP, a more patient-centered approach, focusing on self-monitoring and self-care can facilitate sustainable implementation of symptom monitoring within daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%